Neisseria gonorrhoeae Infections - Pérez-Gracia, María-Teresa; Suay-García, Beatriz (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Gonorrhea is a sexually transmitted infection caused by the obligate human pathogen"Neisseria gonorrhoeae". This Gram-negative diplococcus is highly infective due to its virulence factors: pili, Por proteins, Opa proteins, Rmp proteins, lipooligosaccharides and IgA protease. Despite existing guidelines for its treatment, the incidence of the disease follows an increasing trend worldwide. This is mainly due to the appearance of antibiotic-resistant strains, inefficient diagnostic methods and poor sexual education. Without an effective vaccine available, the key priorities for the control of the disease include sexual education, contact notification, epidemiological surveillance, diagnosis and effective antibiotic treatment. This Special Issue focuses on some of these important issuesm such as the molecular mechanisms of the disease, diagnostic tests and different treatment strategies used to combat gonorrhea.